Conceptualizing English Teacher Identity In Pesantren Based School - Islam, Syaiful; Ilfiah, Ilfiah (Universitas Nurul Jadid, 2024)
This study aims to explore how English teachers at Pondok Pesantren Nurul Jadid conceptualize their professional identity within the unique context of a pesantren-based Islamic school. Employing a survey research method, this investigation gathers data from junior high school English teachers to understand their perceptions and experiences in shaping their teacher identities. The research seeks to delve into the multifaceted nature of teacher identity, considering the interplay of religious values, pedagogical approaches, and the cultural environment of the pesantren. By examining these dimensions, the study aims to uncover how these educators balance their roles as language instructors and moral guides, integrating Islamic teachings with their professional responsibilities. The findings described the interconnectedness of Future Perspective, Teacher Belief, Career Perception, and Self-Efficacy plays a critical role in shaping teacher professional identity. A positive outlook on these aspects encourages teachers to remain committed, resilient, and engaged in their profession. Professional development programs tailored to enhance teacher skills and confidence, along with mentorship opportunities, are essential in reinforcing a strong professional identity. Furthermore, educational policies that prioritize fair compensation, job security, and access to resources create a supportive environment where teachers can thrive. By addressing both internal and external factors that influence professional identity, educational leaders can ensure that teachers feel valued and empowered, ultimately leading to improved job satisfaction, retention, and student outcomes. A focus on these key areas is vital for sustaining a motivated and effective teaching workforce.